SMART-AR: Multimodal Smart Pop-Up Book Based on Augmented Reality with Braille-Voice Over as a Support for Inclusive Learning Media at SDN 2 Bengkala - Sari, Ketut Siti Amerta; Budiarta, I Wayan; Anggarani, Ni Kadek Ayu; Anjelika, Gst. Ayu Kade Widya; Putra, Ida Bagus Semara Adnyana; Widhiana, Kadek; Marselina, Putu Rina; Anastasya, Lorenza (Program Studi PPKn Jurusan Hukum dan Kewarganegaraan Undiksha Singaraja, 2025)
This study developed SMART-AR: Multimodal Smart Pop-Up Book based on Augmented Reality with Braille and Voice Over features as an inclusive learning media at SDN 2 Bengkala. The school faces challenges in inclusive education, particularly the limited number of teachers proficient in sign language and the reliance on conventional learning media that are ineffective for hearing-impaired students. SMART-AR is designed to enhance student understanding, interest, and engagement through an interactive medium combining 3D pop-up books, augmented reality technology, and Braille-voice over support. The development employed the ADDIE model over four months, including needs analysis, design, development, teacher training implementation, and evaluation. Results indicate that 85% of teachers found the media effective in improving student comprehension, 80% reported increased student learning interest, and 78% of teachers felt more confident and ready to continue using the media. SMART-AR offers an innovative solution to overcome the limitations of conventional learning tools and supports more equitable and quality inclusive education at SDN 2 Bengkala. Keywords: Inclusive Education, SMART-AR, Augmented Reality, Braille, Pop-up book